Statistical Application Using Visual Basic For Application (VBA) Excel - Subandi, Subandi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
BandiStats, a statistical application, was developed with the aim of being a simple and easy-to-use statistical analysis tool thanks to its base on Microsoft Excel, a well-known platform. The development method used the Visual Basic for Application (VBA) programming language. The application test results showed the success of all implemented menus. This research produced an application that can facilitate users in analyzing statistical data. It is hoped that this application can be a useful tool for those who need statistical analysis in their daily work without having to have in-depth knowledge of statistics or computer programming. With its easy-to-use interface and comprehensive features, BandiStats provides an efficient and effective solution for statistical data analysis.